CALCULATION OF THE STRESS-STRAIN STATE AND STRENGTH ANALYSIS OF CABLE CONDUIT PIPES IN AIRFIELD PAVEMENT STRUCTURES - Dubyk, Oleksandr; Dashkova, Svitlana; Danilin, Oleksii (Theory and practice of design, 2025)
The article presents the results of a study on the stress-strain state of airfield pavement structures with cable duct pipes embedded within their layers. The interaction of structural elements under the action of self-weight of materials and variable operational loads from modern large take-off mass aircraft is analyzed. Special attention is paid to the influence of pipe positioning within pavement layers on the distribution of stresses and strains, as well as on the overall load-bearing capacity of the structure. The study was carried out using numerical modeling in the SCAD Office soft-ware package. Strength verification of pipes and sleeves was performed, limit values of stresses and strains were determined, and dependencies between geometric parameters of the system and its load-bearing capacity were obtained. The results show that, provided the calculated parameters of pipe wall thickness and protective pavement layers are observed, reliable operation of the cable duct system is ensured without the risk of failure. The practical significance of the study lies in the possibility of applying the obtained data in the design and reconstruction of airfield pavements to ensure their durability and safe operation under conditions of intensive aviation loads. Modern airfield operating conditions are associated with high loads from new-generation aircraft. This necessitates increased reliability of engineering networks, in particular cable ducts arranged within pavement structures. Insufficient attention to their stress-strain state may lead to damage and disruption of system functioning. Modern airfield operating conditions are associated with high loads from new-generation aircraft. This necessitates increased reliability of engineering networks, in particular cable ducts arranged within pavement structures. Insufficient attention to their stress-strain state may lead to damage and disruption of system functioning. Purpose. To assess the stress-strain state and verify the strength of cable duct pipes in airfield pavement structures for different placement options, taking into account the action of permanent and variable loads. Methodology. The research methods are based on the use of the finite element method in calculating the stress-strain state of cable duct pipes in airfield pavement structures. Results. The calculations showed that the studied cable duct structures meet the requirements of strength and operational reliability. The pipe wall thickness and sleeve parameters ensure permissible stresses and strains under loads from modern aircraft (A321 NEO XLR, B737-9 MAX). The obtained results can be used to justify design decisions in the construction and modernization of airfield pavements. Scientific novelty. The scientific novelty lies in the improvement of existing methods for assessing the stress-strain state of cable duct pipes in airfield pavement structures. Practical relevance. The practical significance of the work lies in the possibility of applying the obtained results during the reconstruction and new construction of airfields.